Engineering of Reductive Aminases for Asymmetric Synthesis of Enantiopure Rasagiline - Zhang, Kai; He, Yuanzhi; Zhu, Jiawei; Zhang, Qi; Tang, Luyao; Cui, Li; Feng, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Reductive aminases (RedAms) for the stereoselective amination of ketones represent an environmentally benign and economically viable alternative to transition-metal–catalyzed asymmetric chemical synthesis. Here, we report two RedAms from Aspergillus calidoustus (AcRedAm) and bacteria (BaRedAm) with NADPH-dependent features. The enzymes can synthesize a set of secondary amines using a broad range of ketone and amine substrates with up to 97% conversion. To synthesize the pharmaceutical ingredient (R)-rasagiline, we engineered AcRedAm through rational design to obtain highly stereoselective mutants. The best mutant Q237A from AcRedAm could synthesize (R)-rasagiline with >99% enantiomeric excess with a moderate conversion. The features of AcRedAm and BaRedAm highlight their potential for further study and expand the biocatalytic toolbox for industrial applications.